THE FUNCTION OF MEMORY AND HISTORY IN POSTCOLONIAL LITERATURE (Modern education and development, 2025)
This article examines the functional role of memory and history in postcolonial literature. It analyzes the representation of history and memory in literary works, focusing on their significance in national self-awareness and cultural identification processes in post-colonial literature. The research, conducted within the framework of postcolonial theory, explores the manifestation forms of memory and history in literary texts and their characteristic features.